2012
DOI: 10.1055/s-0032-1331467
|View full text |Cite
|
Sign up to set email alerts
|

Gender Does Matter: Gender-Specific Outcome Analysis of 67,855 Heart Transplants

Abstract: The combination male recipient/female donor carries a higher risk for early mortality, whereas female recipients/male donor reveals favorable short-term results. Gender-matched HT would be ideal, but not suitable in practice because of the shortage of organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…In recent years, there is increasing attention for gender-specific differences regarding prevalence, treatment and outcome of cardiovascular disease. For coronary artery disease and recently for mitral valve surgery as well for heart-transplantation gender-specific differences in outcome are described [ 1 3 ]. There are also well-documented gender differences in abdominal aortic aneurysm disease and outcome after surgical treatment [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there is increasing attention for gender-specific differences regarding prevalence, treatment and outcome of cardiovascular disease. For coronary artery disease and recently for mitral valve surgery as well for heart-transplantation gender-specific differences in outcome are described [ 1 3 ]. There are also well-documented gender differences in abdominal aortic aneurysm disease and outcome after surgical treatment [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the impact of worse renal function on mortality was rather close to the level of statistical significance. The impact of recipient and donor sex on postoperative outcomes has been a point of controversy, as has been the importance of sex-specific donor-recipient matching ( 9 , 11 ). Our study did not support any inferior sex-specific outcomes, but was not powered to investigate the potentially important male to female mismatches among donors and recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Kaczmarek et al [ 41 ] reported the highest 1-year survival in male recipients of male donor hearts (mR/mD: 83.74%). Male recipients of female donor organs (mR/fD: 78.95%) showed the lowest 1-year outcome.…”
Section: Economic Considerations Related To Cardiovascular Risk Factomentioning
confidence: 99%
“…The combination male recipient/female donor carries a higher risk for early mortality, whereas female recipient/male donor reveals favorable short-term results. Gender-matched HTx would be ideal but is not suitable in practice because of organ shortage [ 41 ].…”
Section: Economic Considerations Related To Cardiovascular Risk Factomentioning
confidence: 99%